Policy experimentation and innovation as a response to complexity in China’s management of health reforms - Husain, Lewis (Globalization and Health, 2017)
There are increasing criticisms of dominant models for scaling up health systems in developing countries and a recognition that approaches are needed that better take into account the complexity of health interventions. Since Reform and Opening in the late 1970s, Chinese government has managed complex, rapid and intersecting reforms across many policy areas. As with reforms in other policy areas, reform of the health system has been through a process of trial and error. There is increasing understanding of the importance of policy experimentation and innovation in many of China’s reforms; this article argues that these processes have been important in rebuilding China’s health system. While China’s current system still has many problems, progress is being made in developing a functioning system able to ensure broad population access. The article analyses Chinese thinking on policy experimentation and innovation and their use in management of complex reforms. It argues that China’s management of reform allows space for policy tailoring and innovation by sub-national governments under a broad agreement over the ends of reform, and that shared understandings of policy innovation, alongside informational infrastructures for the systemic propagation and codification of useful practices, provide a framework for managing change in complex environments and under conditions of uncertainty in which ‘what works’ is not knowable in advance. The article situates China’s use of experimentation and innovation in management of health system reform in relation to recent literature which applies complex systems thinking to global health, and concludes that there are lessons to be learnt from China’s approaches to managing complexity in development of health systems for the benefit of the poor.

Logics of Government Innovation and Reform Management in China - Husain, Lewis (STEPS centre, 2015)
Since the beginning of reforms in the late 1970s, China has developed rapidly, transforming itself into a middle-income country, raising hundreds of millions out of poverty and, latterly, developing broad-based social protection systems. The country’s approach to reform has been unorthodox, leading many to talk of a specific Chinese model of development. This paper analyses the role of innovation (chuangxin) and experimentation in the Chinese government repertoire and their contribution to management of change during the rapid, complex and interconnected reforms that China is undergoing. ‘Innovation’ is understood as the process of generation, putting into use, and spread, of new ideas. This contemporary focus on innovation is an extension of an older Chinese government attachment to sub-national initiative in policy formulation and development that goes back to the beginnings of the PRC and before. Central government backing for, and endorsement of, proactive agency on the part of sub-national governments responds to a belief that China is too large, and conditions around the country too diverse, to allow adoption of ‘one size fits all’ policy. Sub-national governments are expected to show initiative in adapting policy locally, and creating locally-useable policy solutions within the overall scope of central policy mandates/ paradigms. The paper argues that innovation by sub-national government is systemically embedded: while central government sets the policy agenda, local governments are frontline managers, and develop a range of policy practices. Differences in conditions between localities mean that multiple variant policy practices are often in circulation at any one time. While innovation is not quantifiable in the aggregate, there is much controlled experimentation, freewheeling innovation, and trial and error, all of which are part of a search for new policy fixes and institutional solutions. Many forms of policy transfer and learning are in evidence, including much central learning from sub-national models, as well as sub-national circulation of a range of innovative policy practices. While much government innovation is not ‘original’, and may be ‘inefficient’ or of little systemic usefulness, overall, the churn of government innovation remains valuable in underpinning systemic adaptation and reform. The paper situates the analysis of government innovation within a larger framework on the functioning of Chinese government and international literature on policy transfer, and outlines an agenda for future research on the structural bases of Chinese government innovation and its contribution to adaptive management.

How did China create “Directed Improvisation”? - Pritchett, Lant (Building State Capability, 2017)
written by Lant Pritchett Yuen-Yuen Ang, a Professor of Political Science at University of Michigan came to speak at Harvard the other day and I was lucky enough to hear her presentation. Her most…
Keywords: IMPORTANT

Evaluation and learning in complex, rapidly changing health systems: China’s management of health sector reform - Xiao, Yue; Husain, Lewis; Bloom, Gerald (Globalization and Health, 2018)
Healthcare systems are increasingly recognised as complex, in which a range of non-linear and emergent behaviours occur. China’s healthcare system is no exception. The hugeness of China, and the variation in conditions in different jurisdictions present very substantial challenges to reformers, and militate against adopting one-size-fits-all policy solutions. As a consequence, approaches to change management in China have frequently emphasised the importance of sub-national experimentation, innovation, and learning. Multiple mechanisms exist within the government structure to allow and encourage flexible implementation of policies, and tailoring of reforms to context. These limit the risk of large-scale policy failures and play a role in exploring new reform directions and potentially systemically-useful practices. They have helped in managing the huge transition that China has undergone from the 1970s onwards. China has historically made use of a number of mechanisms to encourage learning from innovative and emergent policy practices. Policy evaluation is increasingly becoming a tool used to probe emergent practices and inform iterative policy making/refining. This paper examines the case of a central policy research institute whose mandate includes evaluating reforms and providing feedback to the health ministry. Evaluation approaches being used are evolving as Chinese research agencies become increasingly professionalised, and in response to the increasing complexity of reforms. The paper argues that learning from widespread innovation and experimentation is challenging, but necessary for stewardship of large, and rapidly-changing systems.